Impact of the Covid-19 Pandemic on the Financial Performance of Sharia Commercial Banks: an Empirical Evidence from Indonesia - Sugiharto, Toto -; Azimkulovich, Eshmatov Sanjar; Misdiyono, Misdiyono (Universitas Islam Negeri Raden Intan Lampung, 2021)
The Covid-19 pandemic has substantially changed the world. Social, economic, culture as well political landscapes have been forced to adapt to a new normal—a previously unfamiliar or atypical situation that has become standard, usual, or expected. This has, to some degree, obstructed economic activity throughout many sectors, with important aftermaths for businesses and households. Companies that have stopped operating will lose revenue, and, therefore, may not be able to repay the loan. Equally, households where family members lose their job or leave will experience a decrease in income which, in turn, will not be able to pay their loans or credit installments. This phenomenon will result not only in lost revenue but also to losses which has the potential to negatively affect bank profits and capital. This paper is aimed at analyzing the impact of the Covid-19 pandemic towards sharia commercial banks’ performance in Indonesia. The dependent sample t-test was performed to test the proposed hypotheses. It was revealed that the banks’ performances were not totally negatively affected by the Covid-19 pandemic. The growth rate of total assets the capital adequacy ratio (CAR), non-performing financing, and operating efficiency ratio were not negatively affected by this pandemic, however, returns on assets, financing to deposits ratio, and net operating margin were negatively affected by the pandemic.